PENGARUH RELAKSASI OTOT PROGRESIF DAN IMAJINASI TERBIMBING TERHADAP MUAL MUNTAH PADA PASIEN KANKER PAYUDARA - Rizki Dwi Putri; Karolin Adhisty; Antarini Idriansari (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2020)
Nausea and vomiting cause some side effects which can occur in patients after chemotherapy.Progressive muscle relaxation and guided imagery are non-pharmacological actions which can reduceside effects after chemotherapy. The aim of this study was to determine the effect of progressive musclerelaxation and guided imagery on nausea and vomiting in breast cancer patients at Dr. MohammadHoesin Hospital Palembang. The sample was taken by Purposive Sampling technique with inclusioncriteria: Female patients who have breast cancer, PPS breast cancer patients ? 60%, Patients whoexperience nausea or vomiting due to chemotherapy either Acute, Delayed, Anticipatory, Breakthrough,or Refractory. This study used a Pre-Experimental method design with One Group Pretest-PosttestDesign, and an alternative Wilcoxon test was used for data analysis. The results of this study indicatedthat there was an influence of progressive muscle relaxation and guided imagery on the score of nauseaand vomiting with a p-value about 0,000, indicating that the patients were seen relaxed and couldovercome the nausea and vomiting. This research can be applied by using the appropriate StandardOperation Procedure (SOP) which is 2 series in a day for 30 minutes as a non-pharmacological therapyin dealing with nausea and vomiting in breast cancer patients.